2014
DOI: 10.1007/s10495-014-1003-2
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of miR-196a in HIV-associated neurocognitive disorders

Abstract: Involvement of the human immunodeficiency virus type 1 (HIV-1) trans-activator of transcription (Tat) protein in neuronal deregulation and in the development of HIV-1 associated neurocognitive disorders (HAND) has been amply explored; however the mechanisms involved remain unclear. In search for the mechanisms, we demonstrated that Tat deregulates neuronal functions through a pathway that involved p73 and p53 pathway. We showed that Tat uses microRNA-196a (miR-196a) to deregulate the p73 pathway. Further, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 61 publications
2
14
0
Order By: Relevance
“…The rationale for using p73 came from our previous studies, where we showed that Tat protein could induce expression of p53 protein through induction of the p73 protein. We also demonstrated that p53 is a downstream target of p73 and that inhibition of p53 will not affect the endogenous level of p73 (10,38). As seen in Fig.…”
Section: Hiv-1 Tat Protein Alters Neuronal Functionssupporting
confidence: 69%
“…The rationale for using p73 came from our previous studies, where we showed that Tat protein could induce expression of p53 protein through induction of the p73 protein. We also demonstrated that p53 is a downstream target of p73 and that inhibition of p53 will not affect the endogenous level of p73 (10,38). As seen in Fig.…”
Section: Hiv-1 Tat Protein Alters Neuronal Functionssupporting
confidence: 69%
“…The results showed that miR-196a has the potential to provide neuroprotective functions through regulation of the cytoskeleton in HD. Since several studies have addressed the effects of miR-196a on neuronal diseases [ 41 , 42 ], it is anticipated that the results of this analysis based on high throughput screening will provide insights that can aid in the development for therapeutic strategies for treating HD.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these miRNAs are likely involved in key neural processes, such as axonal guidance and glucocorticoid signaling, thus confirming a role for Tat in HIV neuropathogenesis. In addition Tat deregulates neuronal functions by reducing the level of miR-196a, which causes an increase in the Abelson murine leukemia (c-Abl) protein, which phosphorylates the pro-apoptotic transcription factor p73, thus regulating its activity [77]. …”
Section: Regulation Of Mirna Expressionmentioning
confidence: 99%